THE SOCIAL SKILLS OF CHILDREN AND THE CONTENTS THEY WATCH: REFLECTIONS OF THE PANDEMIC PROCESS - Güzelyurt, Tuğçe; Arslan, Hande Hasibe (Inonu University, 2023)
The preschool period is the period in which the child's social skills develop. During this period the child adapts to new environmentand acquires social environment requirements. As distance education rates increased in the Covid-19 epidemic, the social skills expected to be gained by children were adversely affected. In this process, usage of technological tools increased considerably. Thisresearch’s aim is to examine the reflection of the contents that children watch/use during the pandemic process on their social skills in line with family viewswith qualitative survey model and phenomenology design. The study group consists of 25 parents determined by easily accessible situation sampling, whose child receives preschool education (only distance, only face-to-face, distance and face-to-face) in Şırnak provinceThe research datawas collected through interviews and analyzed with descriptive and content analysis techniques. In the research, in line with the participants’ opinionsand research questions six themes were determined as: "Demographic characteristics", "Screen time", "Technological tools used", "Platforms used", "Contents watched/used", "Reflection of contents on social skills". As the result, it has beendetermined that the separation of children from education and friend environment during the pandemic period caused technology usage increaseand negatively affected their social skills. © 2023, Inonu University. All rights reserved.
Çocukların Sosyal Becerileri ve İzledikleri İçerikler: Pandemi Sürecinin Yansımaları
Keywords: Covid-19; Preschool education; Social skills; Technological contents; Technology use